2020
DOI: 10.1371/journal.pone.0228722
|View full text |Cite|
|
Sign up to set email alerts
|

Iron metabolic pathways in the processes of sponge plasticity

Abstract: The ability to regulate oxygen consumption evolved in ancestral animals and is intrinsically linked to iron metabolism. The iron pathways have been intensively studied in mammals, whereas data on distant invertebrates are limited. Sea sponges represent the oldest animal phylum and have unique structural plasticity and capacity to reaggregate after complete dissociation. We studied iron metabolic factors and their expression during reaggregation in the White Sea cold-water sponges Halichondria panicea and Halis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…HRE motifs found in upstream regions of HdF1a and HdF2 (i.a. within CpG islands) presumably make them sensitive to hypoxia [15]; in turn, we have previously shown that hypoxic response is important for sponge reaggregation process [24]. HdF1a, HdF1b, and H. panicea's HpF1, like most Demospongiae and noninsect invertebrate ferritins, have mRNA hairpin motifs of iron-responsive elements (IREs) interacting with the iron-regulatory protein IRP1 (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HRE motifs found in upstream regions of HdF1a and HdF2 (i.a. within CpG islands) presumably make them sensitive to hypoxia [15]; in turn, we have previously shown that hypoxic response is important for sponge reaggregation process [24]. HdF1a, HdF1b, and H. panicea's HpF1, like most Demospongiae and noninsect invertebrate ferritins, have mRNA hairpin motifs of iron-responsive elements (IREs) interacting with the iron-regulatory protein IRP1 (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…The water temperature at the time of collection was and 0 + 2 • C (January), +4 + 5 • C (November) and +12 + 15 • C (August). The sampling was done in a way that sponges remained attached to the substrate (alga), allowing sponge regeneration [24]. Sponges were kept within 7-8 specimens in 5 L aquariums, natural seawater, 2-4 • C or 10-12 • C, and transported to the Koltzov Institute of Developmental Biology (Moscow, Russia).…”
Section: Specimen Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…MFRN (SLC25A37) belongs to the vertebrate mitochondrial solute carrier protein family, which transports various metabolites and cofactors on the MIM. Some researchers show that the MFRN is a carrier of iron ions into mitochondria, and mitochondria of MFRN mutants disrupt iron ion uptake, leading to severe hypochromic anemia and stagnant red blood cell maturation [ 72 , 73 , 74 , 75 ]. In mouse embryonic stem cells, the lack of MFRN causes fibroblasts to stop maturing and inhibits heme synthesis [ 72 ].…”
Section: Mitochondrial Iron Ionmentioning
confidence: 99%